Battling for Hearts and Minds : Memory Struggles in Pinochet's Chile, 1973-1988 - Stern, Steve J., 1951- (Book collections on Project MUSE., 2006)
The story of the dramatic struggle to define collective memory in Chile during the violent, repressive dictatorship of General Augusto Pinochet.